Antimicrobial Activity of Probiotics from Dairy Milk Products against Foodborne Pathogens - Muhammad Fakhruddin Irfan, Sazali (Universiti Malaysia Sarawak, (UNIMAS), 2018)
Probiotic products are one of solution in order to treat and prevent foodborne disease. The efficiency of probiotic in dairy milk products in inhibiting and killing Escherichia coli Ol 57:H7, Vibrio cholera, Bacillus Cereus and Listeria monocytogenes has not been fully elucidated. These foodborne become problematic because theirs resistance towards antibiotics. Consumption of probiotics in daily life can help in improving bowel diseases lead to treat foodborne disease and food safety in food industry. The main objectives of this study to prove the antimicrobial potential of probiotics strains from different source of dairy milk against pathogenic bacteria. Eight brand of probiotic dairy milks was compared. Seven of eight probiotic dairy milks products showed bacteriostatic properties against four strains of foodborne pathogens. Among the tested commercial probiotics products, Yakult and Vitagen showed the most among highest zone of inhibition probiotic in dairy milk products by having 6 mm to 7 mm inhibition zone compared to the control and both show antimicrobial activity. Only Cheddar cheese did not show any antimicrobial properties against foodborne pathogen tested. Therefore, probiotic is good use in the treat and prevent foodbome disease.